Analytical Evaluation of the Diazyme Glycated Serum Protein Assay on the Siemens ADVIA 1800: Comparison of Results Against HbA1c for Diagnosis and Management of Diabetes - Rodriguez-Capote, Karina (J Diabetes Sci Technol, 2015)
BACKGROUND: Hemoglobin A1c (HbA1c) is considered the gold standard for assessment of glycemic control in diabetic patients. HbA1c is inadequate in individuals homozygous or compound heterozygous for hemoglobin variants or in conditions with an altered red blood cell turnover. In these cases glycated albumin (GA) is proposed as an alternative assay. We aimed to evaluate the analytical performance of the Diazyme glycated serum protein (GSP) assay on an automated analyzer, to establish a reference interval (RI), and to compare from a clinical perspective, GSP/GA with glycated Hb (glyHb) results. METHODS: Validation studies followed the CLSI guidelines and included precision, linearity, interferences, concordance of results with glyHb, and RI calculation. GSP was analyzed on representative samples with previously ordered HbA1c and albumin from the DynaLIFE(DX) laboratory. Samples from patients with bisalbuminemia, hemoglobinopathies, and multiple myeloma were also included. RESULTS: Within-run and total imprecision was <3.0% at both levels of control, analytical sensitivity was 5.31 μmol/L, and linearity was verified from 10 to 1150 μmol/L (total allowable error of 5%). Clinical concordance between %GA and glyHb was substantial (n = 175, R(2) = .91, kappa = .78, P = .167). GSP RI was 160 to 340 μmol/L or if expressed as %GA 10.5 to 17.5%. CONCLUSION: Analytical performance of the Diazyme GSP assay on the Siemens ADVIA 1800 is acceptable for clinical use. The RI obtained was higher than that suggested by the manufacturer.